2022
DOI: 10.7554/elife.76077
|View full text |Cite
|
Sign up to set email alerts
|

An expanded toolkit for Drosophila gene tagging using synthesized homology donor constructs for CRISPR-mediated homologous recombination

Abstract: Previously, we described a large collection of Drosophila strains that each carry an artificial exon containing a T2AGAL4 cassette inserted in an intron of a target gene based on CRISPR-mediated homologous recombination (Lee et al., 2018). These alleles permit numerous applications and have proven to be very useful. Initially, the homologous recombination-based donor constructs had long homology arms (>500 bps) to promote precise integration of large constructs (>5kb). Recently, we showed that in vivo li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“… Kanca et al (2022) showed that SSA can be used for CRISPR/Cas9 genome engineering in Drosophila . Although these authors achieved success with only 200 bp of homology on each side of the DSB our work suggests that increasing this will enhance the success of integration, yielding more efficient gene edits per round of embryonic injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Kanca et al (2022) showed that SSA can be used for CRISPR/Cas9 genome engineering in Drosophila . Although these authors achieved success with only 200 bp of homology on each side of the DSB our work suggests that increasing this will enhance the success of integration, yielding more efficient gene edits per round of embryonic injections.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into how Marcal1 promotes SSA through its annealing activity, we asked how changing the length of available complementarity would affect SSA efficiency in both wild-type and Marcal1 mutant flies. This question is also of interest because SSA can be used for CRISPR/Cas9-based genome editing to incorporate fragments into the Drosophila genome ( Kanca et al 2022 ). Demonstration of this approach employed a plasmid with 200 nt of flanking homology to either side of 2 Cas9 genomic targets.…”
Section: Introductionmentioning
confidence: 99%
“…The lower rescuing capacity of patient variants corroborated a LOF effect. As not all genes are suitable targets for CRMIC-based integration of a trojan exon, the gene can also be replaced completely by a GAL4-expressing sequence ( Kanca et al, 2022 ). Large libraries of flies with integration sites in different genes provide broad access to the Drosophila genome ( Venken et al, 2011 ; Nagarkar-Jaiswal et al, 2015 ; Lee et al, 2018 ).…”
Section: Drosophila Genetics and Tools To Investigate Seizur...mentioning
confidence: 99%
“…CRISPR can also be used to generate mutations that are allelic orthologs to specific human disease mutations, to functionally inhibit gene/protein function in particular tissues for assessment of cell- and tissue-specific phenotypes, and to assess expression patterns and subcellular protein localization. CRISPR technology has been used to create multiple disease models by insertion of the yeast GAL4 gene in flies ( Lee et al, 2018 ; Kanca et al, 2019 , 202 1), worms ( Wang et al, 2017a ) and, to some extent, mice ( Clark et al, 2020 ). Embryonic lethal mutant phenotypes may be pursued using cell- or tissue-specific knockouts, which are more easily applied to invertebrates and zebrafish, the externally growing embryos of which allow the facile study of mutant phenotypes at cell resolution prior to death.…”
Section: Forward and Reverse Genetic Screensmentioning
confidence: 99%